Molecular studies of an X;Y translocation chromosome in a woman with deletion of the pseudoautosomal region but normal height - Spranger, Stephanie; Kirsch, S.; Mertz, A.; Schiebel, Katrin; Tariverdian, Gholamali; Rappold, Gudrun (Clinical genetics, 1997)
A translocation chromosome in a woman with the karyotype 46,X,der(X)t(X;Y)(p22.3; q11.2) was investigated by FISH and STS analysis with molecular probes derived from the sex chromosomes. Due to the partial deletion of the short arm pseudoautosomal region (PARI) from DXYS14 to DXYS147 in the translocation chromosome, the proband is hemizygous for the gene responsible for growth control (SS) located in this region, yet does not show growth retardation. Molecular analysis of the Yq arm of the translocation chromosome revealed the presence of markers DYS273 to DYS246 harboring the hypothesized growth control gene critical region (GCY) on Yq, thereby placing the deletion breakpoint between markers DYS11 and DYS273. These results suggest that the Y-specific growth gene GCY on Yq compensates for the missing growth gene SS on Xp22.3.
Elektronische Reproduktion der Druck-Ausgabe
Online: 28 June 2008
Gesehen am 30.03.2021